Differences of Sexual Function: A Study in Two Menopause Groups - Luh Ari Arini (Universitas Ngudi waluyo, 2020)
Menopause is a period where the reproductive cycle has stopped in women and is characterized by a permanent menstrual cessation, due to a decrease in the function of reproductive organs such as the ovaries as a sex steroid hormone (estrogen and progesterone) which plays an important role in the reproductive cycle. The decrease in hormones during menopause causes problems in sexual function such as decreased interest in sexual relations due to vaginal lubrication problems, this can be overcome by doing light physical exercise. Light exercise or physical activity when entering menopause is known to have a positive effect on the quality of life of menopause, including on sexual function. The purpose of this study was to determine differences in sexual function between menopausal women who exercise or do physical activity and who do not exercise. This research method is a conceptual study or literature study from previous research relating to exercise and sexual function at menopause. The results of the study showed that menopausal women who routinely exercise or physical activity, their sexual function is better than those that are not, it is known that menopausal women feel very satisfied with their sexual lives and have no problems during intercourse with their partners. Menopausal women have to exercise regularly, besides consuming healthy foods with balanced nutrition, because the more frequent and regular exercise, the sexual life of menoapause women will be much better.